PENGEMBANGAN SISTEM INFORMASI AKADEMIK UNIVERSITAS SAHID SURAKARTA - Farid Fitriyadi; Sri Huning Anwariningsih; Astri Charolina (Universitas Sahid Surakarta, 2015)
Academic Information System (SIAKAD) is the applications which are designed and made to process data-data related to academic information, to data students,employees, the curriculum, and lecture schedule. Each member designed exclusively has different access to SIAKAD. High access that is meant to suit your needs and highinterest of each and every user's system.Testing SIAKAD use methods webqual, the method webqual is one of the methods or technical quality measurement website based on perception end users. The methodWebqual has started to develop since the year 1998 and has experienced some interaction in arranging. The method Webqual ordered based on research in nineareas, namely: quality Information Quality ), quality Interaction (Interaction Quality).